Knowledge, risk perception and protection behavior among Malaysian young adults during COVID-19 pandemic - Gan, Hui Min; Tan, Jeanette Elena; Swi, Zi Qing (2022)
In recent years, a novel infectious disease, COVID-19, has spread worldwide includes in Malaysia. This air-borne disease (COVID-19) causes illnesses ranging from the common cold to severe diseases. Individuals are required to practice protective behaviour to reduce the risk of getting infected. A previous study mentioned that an individual’s knowledge and risk perception of COVID-19 could contribute to the engagement of protective behaviour. Hence, our study aimed to examine the role of risk perception as a mediator between knowledge and protective behaviour of COVID-19. Furthermore, our study also hypothesized that knowledge predicts an individual's protective behaviour through risk perception as a mediator. The study was conducted using a cross-sectional survey design. A total of 323 young adults (Mean age = 21.89; SD = 1.513) were recruited via the purposive sampling method. The collected data was tested with linear regression to analyse the predicting effects of the variables, and PROCESS Macro was run mediation analysis. The regression model result found that knowledge (β = .026, p = .640) does not significantly predict risk perception; knowledge (β = .082, p = .140) does not significantly predict protective behaviour; while only risk perception (β = -.112, p = .044) significantly predicted protective behaviour among young adults in Malaysia. Besides, the findings of mediation analysis showed no significant mediating effect of risk perception on knowledge and protective behaviour. Since there is limited research in Malaysia regarding the determinants of protective behaviour, this study broadens the research perspective in this relevant field in Malaysia context and contributes substantial knowledge for further study.